2018
DOI: 10.30684/etj.36.10a.8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Multi-Walled Carbon Nanotubes Decorated with Zinc Oxide Nanoparticles for Removal of Pathogenic Bacterial

Abstract: A series of Zinc Oxide Nanoparticles (ZnONPs)-functionalized Multi-Walled Carbon Nanotubes (F-MWCNTs) Nano composites were developed as antibacterial. In this study, chemical oxidation of pristine MWCNTs were carried out with a mixture of strong acids (3H2SO4 98%:1 HNO3 65%).The F-MWCNTs were used as templates to prepare hybrid material like ZnONPs decorated F-MWCNTs. Pristine MWCNTs, F-MWCNTs and (ZnONPs/F-MWCNTs) Nano composites powder were investigated using Fourier Transform Infrared spectroscopy (FTIR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In contrast to other antibacterial films, this film performed particularly well after 12 hours of cultivation. These results clearly showed that TiO2 and ZnO have a greater ability to resist bacteria growth [38][39][40][41][42][43]. 2.0 2.5 0.13 ± 0.02 0.12 ± 0.00577 The results are means of three replicates; ±, standard deviation (SD).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…In contrast to other antibacterial films, this film performed particularly well after 12 hours of cultivation. These results clearly showed that TiO2 and ZnO have a greater ability to resist bacteria growth [38][39][40][41][42][43]. 2.0 2.5 0.13 ± 0.02 0.12 ± 0.00577 The results are means of three replicates; ±, standard deviation (SD).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Researchers found that additional materials could be added to dielectric material systems, such as semiconductor powders, to improve their performance [8], [9]. Random lasers have been used in numerous applications such as uid crystals [10,11], polymer materials [12], [13], human tissues [14], bone tissues [3] and bres [15]. In addition to fewer predicted spectroscopy, a speck-free projection, and a wide range of holographic laser diagnosis are presented [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%